INTEGRATION OF DIGITAL INNOVATION IN HIGHER EDUCATION MANAGEMENT TO SUPPORT THE ACHIEVEMENT OF SDGs 4 (QUALITY EDUCATION): A STUDY OF THE DEVELOPMENT OF A MODEL TO IMPROVE ACADEMIC COMPETITIVENESS IN THE ERA OF SOCIETY 5.0 - Asrul; Muh. Amir; La Ode Agus Said; Muh. Rijal; Sarinah (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
The development of digital technology has driven significant changes in various sectors, including higher education. Universities are required to adapt to technological developments to improve the quality of governance, learning processes, and academic competitiveness at the national and global levels. In the context of the Society 5.0 era, the integration of digital innovation in higher education management is a crucial strategy for creating a more adaptive, efficient, and community-oriented education system. This study aims to analyze the integration of digital innovation in higher education management and develop a management transformation model capable of enhancing the academic competitiveness of universities. This research is also directed at supporting the achievement of the Sustainable Development Goals (SDGs), specifically SDG 4 on quality education, which emphasizes the importance of improving the quality of education through innovation and technology. The research method used is a mixed methods approach, namely a combination of quantitative and qualitative methods. The quantitative approach is used to examine the relationship between the variables of digital innovation integration in management and increased academic competitiveness through surveys of lecturers, education staff, and university leaders. Meanwhile, the qualitative approach is carried out through in-depth interviews and document analysis to gain a more comprehensive understanding of the practice of digital innovation-based higher education management transformation. The expected outcome of this research is the identification of key factors influencing the successful integration of digital innovation into higher education management and the development of a conceptual model that can be used as a reference for improving the academic competitiveness of higher education institutions in the Society 5.0 era. In addition to providing theoretical contributions to the development of higher education management science, this research is also expected to provide strategic recommendations for policymakers in designing more innovative, adaptive, and sustainable higher education governance.